2013
DOI: 10.1590/s0100-69912013000100003
|View full text |Cite
|
Sign up to set email alerts
|

O efeito em curto prazo do bypass gástrico sobre pacientes obesos diabéticos

Abstract: Obese patients with DM2 undergoing gastric bypass showed improved glycemic control and reduced use of hypoglycemic agents in the short-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
(38 reference statements)
0
6
0
4
Order By: Relevance
“…A variety of treatment options exist for the management of insulin resistance, including a multidisciplinary clinical approach designed to promote weight loss, pharmacological therapies, and bariatric and metabolic surgical techniques 15 , 17 - 18 . Ileal transposition involves the removal of a segment of the distal ileum and its insertion into the proximal small intestine, a procedure that promotes early satiety and exerts beneficial effects on glucose metabolism and weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of treatment options exist for the management of insulin resistance, including a multidisciplinary clinical approach designed to promote weight loss, pharmacological therapies, and bariatric and metabolic surgical techniques 15 , 17 - 18 . Ileal transposition involves the removal of a segment of the distal ileum and its insertion into the proximal small intestine, a procedure that promotes early satiety and exerts beneficial effects on glucose metabolism and weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Roux-en-Y gastric bypass (RYGB) has a rapid and drastic effect in type 2 diabetic patients, many of whom show complete remission within days of the procedure [1, 2]. A number of studies have demonstrated that gut hormones, especially GLP-1, may play a pivotal role in the regulation of glucose metabolism in response to this surgery [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…As cirurgias gastrointestinais podem promover a melhora do controle glicêmico por meio da restrição alimentar e da perda de peso, assim os procedimentos cirúrgicos que induzem a perda de peso também podem promover a remissão do DM2 consideravelmente entre indivíduos obesos mórbidos (CELIK et al, 2015). A resolução sustentada do DM foi observada em pacientes com histórico de menor duração da doença previamente à Cirurgia Bariátrica, ou seja, quanto mais cedo for realizada a intervenção cirúrgica no obeso portador de DM, maiores as chances de remissão total do DM e manutenção dos níveis glicêmicos (STOLL et al, 2013). Neste estudo os indivíduos obesos foram submetidos à Cirurgia Bariátrica por meio de técnica mista, restritiva e disabsortiva.…”
Section: Características Sociodemográficas Comorbidades Hábitos De unclassified
“…Os pacientes DM portadores de periodontite no pré-operatório apresentaram redução na severidade do desfecho, fato provavelmente mediado pelo controle dos parâmetros metabólicos e diminuição significativa do peso (CAMBI et al, 2015;CELIK et al, 2015;CHENG et al, 2014;STOLL et al, 2013). Em G2, também foi observada a redução na periodontite no período PO 6m, porém ao final das avaliações (PO 12m) as diferenças com os obesos em G1 foram minimizadas, apresentando a mesma chance de ocorrer a periodontite (Tabela 6).…”
Section: Condições Periodontais E De Higiene Bucalunclassified
See 1 more Smart Citation